WAYANG SEBAGAI SUMBER INSPIRASI DAN ENERGI DALAM SASTRA INDONESIA MODERN: ANALISIS GENETIS RESEPTIF - Edy Sutanto (Populis : Jurnal Sosial dan Humaniora, 2016)
Wayang  was born almost 34 century ago and modern Indonesian  literatur was born almost a century ago. As integral part of modern society as well as an imagiation and creativity, literature also carries a social funtion. At certain periods literature can also be functioned as conservation of national enthusiasm, law,economic, convention, ethics, and other social systems. Modern Indonesian Literature, especially when it is viewed through its caracterization element is conceptually a combination between modernization and tradition. Its form, content, and narative structure were influenced by Western literary tradition, novelistic convention. Where as its energy its archetypal structure, were taken from east, thrugh wayang world. Keywords: novel, wayang, esthetics, archetype, literature,  tradition.